PENGEMBANGAN BAHAN AJAR TEMATIK MEDIA PEMBELAJARAN BERBASIS LECTORA INSPIRE PADA KELAS IV SDN CILEGON 1 - Fitriatul Muthaharoh; Aan Subhan Pamungkas; Trian Pamungkas Alamsyah (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2019)
The study aims to develop thematic teaching materials in the form of lectora inpire-based learning media in the environmental sub-themes where I live. The subjects of this study werw fourth grade students of SDN Cilegon 1 Academic Year 2018-2019. The feasibility of this product was based on the validity level of lectora inspire-based thematic teaching materials, user responses to lectora inspire thematic-based teaching materials and student understanding after using lectora thematic-based thematic teaching materials inspire. Data collections techniques used questionnaire sheets, questionnaires and student response questionnaires, student comprehension test sheets and documentation. The result of the reseacrh that have been done are (1) the average score of the validation of the expert team is obtained with a percentage of 92.74% which is included in the category of “very feasible” (2) the average score of students responses with a percentage of 94.07 included in “very decent” category (3) post test average score of 88 which has reached the KKM value in the category of “very good” so it can be concluded that thematic teaching material in the form of lectora inspired-based learning media is suitable to be used in the environmental subtme where I live in class IV and can provide understanding to fourth grade student especially on thematic learning.